The role of alcohol dependency in deaths among people with epilepsy recorded by the National Drug-Related Deaths Index (NDRDI) in Ireland, 2004–2013. (February 2017) - Lynn, Ena; Lyons, Suzi; Langan, Yvonne; Craig, Sarah; Doherty, Colin
Highlights: Alcohol dependent persons with epilepsy require a more considered approach to treatment in the clinical setting. Epilepsy treatment plans must be family inclusive and incorporate appropriate management of seizures. Discussion on the risks of comorbidities and mortality should be incorporated into epilepsy treatment plans. In a number of situations the person was not alone therefore some deaths may have been prevented if appropriate first aid was administered. There is an opportunity to provide more accurate data on epilepsy-related deaths by extending the remit of the NDRDI to include these deaths. Abstract: Purpose: The aim of this study was to investigate deaths among individuals with epilepsy recorded on the National Drug-Related Deaths Index (NDRDI). Method: A descriptive analysis of individuals with a known history of epilepsy in the NDRDI from 2004 to 2013 was undertaken. Results: Between 2004 and 2013, 225 (2%) of the recorded cases had a documented history of epilepsy, 82 (36%) of whom had epilepsy recorded as the cause of death. Of these 82 deaths, the majority were male (60–73%) and half (median age) were aged 47 years or younger. A post mortem toxicology report was available for 65 (79%) of these deaths, of which over two thirds (44–68%) did not have any antiepileptic drugs present on toxicology. Over two thirds of these deaths, (31–70%) were among people known to be alcohol dependent. Conclusion: The high percentage of individuals with a diagnosis of alcohol dependency that died as a result of epilepsy and who have no antiepileptic drugs in their system at the time of their death, highlights the need for preventative measures for this at-risk group.